Groundwater Model as a Tool for Sustainable Groundwater Management - Adnan, Mohd Shalahuddin; Hendrayana, Heru; Ekaputra, Doni Prakasa (International Journal of Integrated Engineering, 2013)
: Groundwater could be regard as on of vital water resource due to high quality and perennial availability. However, lack of sustainable approach in  groundwater management has induced a negative impact as evidenced by falling water tables, dryingwetlands, increasing sea-water intrusion and deterioration of water quality. As groundwater cannot be renewed artificially on a large scale, sustainable management of this resource is vital. A number of scientific tools was applied for a number of applications such as assisting stakeholder in making decision, groundwater flow model, particle tracking and many more. In this paper, Semarang Urban Area case study will be used as example in illustrate the uses of groundwater modeling in achieving sustainable groundwater management. Three items are discussed here to promote the advantages of groundwater modeling.